Improving Students’ Science Process Skills on Biology Using Bounded Inquiry Lab Model - HANDAYANI, SIN SYIN LU’LU’; SUCIATI, SUCIATI; MARJONO, MARJONO (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2016)
This research is to improve the students’ science process skills include four aspects: 1) formulating problem; 2)formulating hypotheses; 3) constructing experimental design; 4) apply concept in Senses System,by applying boundedinquiry lab model for second grade students at SMA Al Islam 1 Surakarta. This research is a classroom action research(CAR), conducted in two cycles. Each cycle consists of planning, action, observation, and reflection. The research subjectwas 35 students of science 3 at SMA Al Islam 1 Surakarta.Data collection techniques used: 1) non-test technique(observation, interviews, and documentations); 2) test for science process skills. Data was analysed using descriptivequalitative. The results show that there is an improvement of each aspect of science process skillsfrom Pre-Cycle to Cycle2, i.e. formulating problem (39,46%; 50%;82,35%); formulating hypotheses (34,05%; 49,12%; 81,48%); experimentaldesign 34,05%; 49,12%; 81,48%); application concept (36,76%; 38%; 64,75%).Itcanbe concluded that the application ofbounded inquiry lab model can improve students’ science process skills.